2022
DOI: 10.1111/jonm.13574
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of residents, family members and staff in residential care settings for older people during COVID‐19: A mixed methods study

Abstract: Aim The aim of this study was to explore the COVID‐19 pandemic as it was experienced by people on the front line in residential care settings for older people in the Republic of Ireland (ROI). Background The COVID‐19 pandemic had a disproportionate effect in residential care settings for older people in Ireland. Methods A two‐phased mixed methods study was conducted, consisting of an online survey administered shortly after the first wave of the virus to staff, residents and family members and one‐to‐one inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…We found increased concern about the wellbeing of a close relative living in a nursing home to be extremely common—a result which mirrors previous research [ 42 – 44 ]. However, our exploratory research adds to knowledge on the precise factors associated with experienced concern among nursing home residents’ FMs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found increased concern about the wellbeing of a close relative living in a nursing home to be extremely common—a result which mirrors previous research [ 42 – 44 ]. However, our exploratory research adds to knowledge on the precise factors associated with experienced concern among nursing home residents’ FMs.…”
Section: Discussionsupporting
confidence: 89%
“…Frequent visitors may feel personally responsible for the care [ 6 ] and thus also feel increased concern when they are prevented from visiting. As previous COVID-research demonstrates [ 44 ], the loss of such a caregiving role proved a major source of distress to family members during the visiting ban. It is also worth noting that Finnish nursing homes seldom offer distinct visiting hours; rather, FMs may visit when they choose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it was mostly families who communicated the need for virtual visits, reporting the challenges they experienced depending on the availability of staff or who was on duty that day. Sweeney et al, [ 27 ] reported similar findings, with family members placing greater emphasis on maintaining virtual contact with their relatives. Our findings reflect other qualitative research studies where relatives of older adults living in RCS reported feeling anxious and concerned about their family members’ psychological well-being during the lockdown period [ 18 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 80%
“…Sweeney et al, [ 27 ] reported similar findings, with family members placing greater emphasis on maintaining virtual contact with their relatives. Our findings reflect other qualitative research studies where relatives of older adults living in RCS reported feeling anxious and concerned about their family members’ psychological well-being during the lockdown period [ 18 , 27 , 28 ]. Staff also found the requests for virtual visits from visitors at times to be demanding and an extra burden on their workload, especially due to understaffing and competing caring priorities.…”
Section: Discussionmentioning
confidence: 80%